Analysis of Competency of Village Apparatuses, Organizational Commitment, and Clarity of Budget Targets Based on the Basic Values of Islamic Leadership on the Accountability of Village Fund Management in Batauga District, South Buton Regency - Rais, Muhammad (International Journal of Management Progress, 2022)
Accountability for managing village funds is an obligation for the village government. Problems that occur in the management of village funds are related to the competence of the village apparatus, organizational commitment, and targets. This study aims to determine the effect of village apparatus competence, organizational commitment, targets for accountability in village fund management in Batauga Sub-district Village. This study collected data using a questionnaire with a sample of 30 people. The data analysis technique used multiple linear regression which was processed using SPSS. The results of this study indicate that the competence of the village apparatus and the target of excellence have a significant and positive effect on the accountability of village fund management. Meanwhile, organizational commitment has no significant effect on the accountability of village fund management. In addition, the adjusted R square value is 0.248 or 24.3%, which means the ability of the independent variable to explain the variable is only 24.3% and 75.7% is explained by other variables